The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/ece3.9142
|View full text |Cite
|
Sign up to set email alerts
|

Extensive sharing of chloroplast haplotypes among East Asian Cerris oaks: The imprints of shared ancestral polymorphism and introgression

Abstract: Shared ancestral polymorphism and introgression are two main causes of chloroplast DNA (cpDNA) haplotype sharing among closely related angiosperms. In this study, we explored the roles of these two processes in shaping the phylogeographic patterns of East Asian Cerris oaks by examining the geographic distributions of randomly and locally distributed shared haplotypes, which coincide with the expectations of shared ancestry and introgression, respectively. We sequenced 1340 bp of non‐coding cpDNA from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 140 publications
0
11
0
Order By: Relevance
“…3 ) is also supported by evidence from previous molecular studies. First, all modern Cerris share the same, section-unique plastid lineage, indicative of a single point of origin and quick dispersal, with the East Asian subsection Campylolepides showing the overall highest plastid divergence ( Simeone et al , 2018 ; Zhang et al , 2020 ; Li et al , 2022 ). Second, the Cerris plastomes are part of a haplotype lineage shared with a group of section Ilex species thriving in modern-day Japan and the mountains of northern and central China (East Asian clade in Figs 1 and 3 ; Simeone et al , 2016 : Quercus engleriana Seemen, Q. phillyreoides and Q. spinosa David; Zhou et al , 2022 : Quercus dolicholepis , Q. engleriana , Q. spinosa and Q. pseudosetulosa Q.S.Li & T.Y.Tu), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…3 ) is also supported by evidence from previous molecular studies. First, all modern Cerris share the same, section-unique plastid lineage, indicative of a single point of origin and quick dispersal, with the East Asian subsection Campylolepides showing the overall highest plastid divergence ( Simeone et al , 2018 ; Zhang et al , 2020 ; Li et al , 2022 ). Second, the Cerris plastomes are part of a haplotype lineage shared with a group of section Ilex species thriving in modern-day Japan and the mountains of northern and central China (East Asian clade in Figs 1 and 3 ; Simeone et al , 2016 : Quercus engleriana Seemen, Q. phillyreoides and Q. spinosa David; Zhou et al , 2022 : Quercus dolicholepis , Q. engleriana , Q. spinosa and Q. pseudosetulosa Q.S.Li & T.Y.Tu), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic and anatomic data analysis indicated that oaks might have different defense mechanisms against pathogens [ 29 ]. Chloroplast DNA (cp.DNA) markers from Q. acutissima , Q. chenii , and Q. variabilis revealed haplotype sharing within section Cerris in East Asian EBLFs that was associated with locally stable climates and complex landscapes [ 30 ]. Based on SSR and phenotypic data in two oak species indicated that asymmetric inter-specific selection pressures could contribute to the asymmetric trait divergence where species coexist [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chloroplast (cp) DNA has been widely used to track the historical gene flow among closely related oaks [6,[17][18][19][20][21][22][23][24][25][26][27][28][29]. It is expected to be more frequently introgressed than nuclear DNA because maternally inherited cpDNA is dispersed only by seeds and thus experiences a low level of intraspecific gene flow, which would hinder the immediate dilution of introgressed genotypes [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, cpDNA variation patterns of oaks, more likely reflecting the imprints of localized interspecific gene flow, are largely influenced by geography rather than by taxonomy [31,32]. Previous studies have shown that interspecific sharing of geographically restricted cpDNA haplotypes occurred within section Quercus [18][19][20][21], section Lobatea [22], section Virentes [23], section Cerris [6,[24][25][26], section Ilex [6,[27][28][29], and section Cyclobalanopsis [29]. Chloroplast capture events between sections were rare but also reported for sections Quercus and Ponticae, sections Quercus and Virentes, and sections Quercus and Protobalanus [17,32], probably tracking the history of ancient introgression between ancestral populations of oaks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation